Comparative effectiveness of the ethanol extract and infusion of green tea leaves (Camellia Sinensis L.) as a diuretic in male swiss mice - Agustina Susilowati; Sista Nanda Indratika (Universitas Ahmad Dahlan, 2020)
Green tea (Camellia sinensis L.) contains flavonoid compounds and methylxanthine and has proven efficacy as a diuretic. The dosage form is among the factors determining the biological effects of a drug. This experimental study set out to determine the effectiveness of the ethanol extract and infusion of green tea leaves as a diuretic in male Swiss mice. A total of 20 male Swiss mice were divided into four groups receiving different daily treatments: group I (given 1% Na-CMC), group II (furosemide at a dose of 5.2 mg/kg BW), group III (ethanol extract of green tea leaves at a dose 70 mg/kg BW), and group IV (green tea leaf infusion at a dose of 70mg/kg BW). Before the treatment, all groups were given warm water orally (0.4 ml/20g BW), then the effects of diuretics were measured from urine volume for six hours. The data were analyzed statistically by one-way analysis of variance (ANOVA), followed by LSD comparison tests, with p<0.05 indicating any significantly different means. Based on the phytochemical screening results, the ethanol extract and infusion of green tea leaves contained alkaloids, flavonoids, and tannins. The mean cumulative urine volume in group I was 0.260±0.185 ml, group II 0.869±0.162 ml, group III 0.866±0.197 ml, and group IV 0.642±0.187ml. Compared to furosemide, the diuretic activity of the ethanol extract of green tea leaves (0.997±0.182) was not significantly different (p>0.05) from that of the green tea leaf infusion (0.739±0.182). In conclusion, green tea leaves can be used as diuretics in two dosage forms, namely extract and infusion.